Towards a Sustainable Employment Relationship for Public Universities in Malaysia - Badariah Ab Rahman; Dzurizah Ibrahim; Rosazman Hussin (2019)
This paper discusses the workplace partnership practices in Malaysia through the Academic Staff Associations (AJCC) at a public universities in Malaysia. Extensive literature have argued that workplace partnership such as the JCC has the capacity to increase job satisfaction, reduce industrial disharmony, increase organizational commitment and improve employee relations in general. The study is focusing on two aspects; (i) the importance of workplace partnership mechanism in public universities in Malaysia; and (ii) the influence of the workplace partnership practice to the organizational decision making in public universities in Malaysia. This study employs qualitative case studies in which interviews were conducted at the respective universities. However, the study reveals that a loose partnership arrangement existed between the Academic JCCs-management and vice versa. This study has established that the desire to move forward is being felt but still concerned with who is the authority (power). As long as this power issue is the case, this research argues that the management will continue to make final decisions; thus will preserve its supremacy as the single authority in public universities in Malaysia. The result warrants some amendments toward the current policy with regards to the role and function of the Academic JCCs because it is important for the two parties to work in partnership instead of being treated as separate entities in organizations. This study recommends a new form of partnership in order for sustainable partnership arrangements for a better working environment.